Current Challenges in Hepatitis B - Ahad, MA; Alim, MA (TAJ: Journal of Teachers Association, 2011)
Viral hepatitis and its sequelae is one of the important causes of mortality and morbidity world wide. Hepatitis B is a major cause of chronic liver disease and a significant public health issue. Between 350 million to 400 million people world wide chronically infected with HBV. The HBV prevalence in Bangladesh is 2.3 to 9.7 % with an approximate carrier of 10 million. The prevention and treatment of hepatitis B possess a great challenge. doi: 10.3329/taj.v19i1.3168 TAJ 2006; 19(1): 38-44